Diseño y construcción de una aerobomba tipo molino multipala americano para el laboratorio de Energías Renovables del A.E.I.R.N.N.R. - Tinoco Córdova, Mario Ramiro (2012)
This research paper entitled "DESIGN AND CONSTRUCTION OF A KIND WINDPUMP MULTIBLADE MILL AMERICAN LABORATORY AEIRNNR Renewable Energy", after gathering the information inherent in the subject, is divided into four chapters. In the first chapter, referring to the history of the use of wind power and windmills, since the dawn of civilization to the present time in the world, their generalizations, applications, advantages and disadvantages. The second chapter describes the formulation and mathematical model for the dimensioning of windmills used according to the technical requirements and availability of the wind resource. In this chapter, it makes wind resource assessment to determine the energy potential of the area, as also described instruments to measure wind speed and wind direction. In the third chapter gives the results obtained after the activities undertaken in the previous chapters, with data reporting practices with wind pump. The fourth and final chapter will present the conclusions and recommendations can be suggested when implementing a project of this nature. As well as including the annexes, photos and drawings.